Global, regional, and national burden of older adult atopic dermatitis in 204 countries and territories worldwide - Ou, Yi; Shao, Xinyi; Zhang, Jingbo; Chen, Jin (Frontiers in Public Health, 2025)
BackgroundWith the aging global population, older adult atopic dermatitis (AD) is emerging as an increasingly significant health challenge. This study aimed to evaluate the global burden of older adult AD from 1990 to 2021 and to project its change to 2050.MethodsThe estimates and 95% uncertainty intervals of prevalence, incidence, and disability-adjusted life-years (DALYs) attributable to AD among individuals aged over 60 years were extracted from the Global Burden of Diseases (GBD) Study 2021. We used joinpoint regression analysis, decomposition analysis, cross-country inequality analysis, frontier analysis and prediction model to epidemiological analysis.ResultsFrom 1990 to 2021, the global prevalence of older adult AD increased to 11,009,630 cases (95% UI: 9,915,829 to 12,170,941), even as ASRs declined, which were primarily driven by population growth. It was observed that females and 75–79 years old had higher incidence rates. SDI relative and frontier analysis exhibited that incidence, prevalence and DALYs rates were positively correlated with SDI levels, while SDI-related inequalities had a significant decrease. Predictions up to 2050 anticipated increasing older adult AD incidence, prevalence, and DALYs numbers, while only age-standardized disability-adjusted life-year rates (ASDRs) were expected to decline.ConclusionThe burden of older adult AD varied by genders, age groups, regions, countries and climatic conditions. Although the ASRs had shown a decline over time, the burden of older adult AD remained significant, especially in regions with high SDI levels. In the future, the burden of older adult AD was projected to continue rising until 2050, thereby targeted interventions and public health strategies were needed to address this trend.